2019
DOI: 10.1111/jcpt.13036
|View full text |Cite
|
Sign up to set email alerts
|

Macroprolactinaemia modulates cardiometabolic effects of fenofibrate in men with atherogenic dyslipidaemia: A pilot study

Abstract: What is known and objective: Cardiometabolic effects of hypolipidaemic agents depend on plasma levels of monomeric prolactin. Although macroprolactinaemia seems to be associated with increased cardiometabolic risk, no previous study has investigated whether macroprolactinaemia modulates pleiotropic effects of hypolipidaemic agents. Methods: The study population included two age-, weight-, blood pressure-and lipidmatched groups of men: 12 men with elevated levels of big-big prolactin and 16 men with prolactin l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Negative predictors of the changes in hormone levels and antibody titers in our study were total prolactin levels and macroprolactin content, inversely correlating with levothyroxine action. Interestingly, both prolactin before polyethylene glycol precipitation and big‐big prolactin were found to be sensitive markers for hypolipidemic and pleiotropic effects of hypolipidemic drugs in our previous studies 12,13 . The presence of a correlation between macroprolactin and total prolactin in women with macroprolactinemia indicates that both variables were reciprocally related.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Negative predictors of the changes in hormone levels and antibody titers in our study were total prolactin levels and macroprolactin content, inversely correlating with levothyroxine action. Interestingly, both prolactin before polyethylene glycol precipitation and big‐big prolactin were found to be sensitive markers for hypolipidemic and pleiotropic effects of hypolipidemic drugs in our previous studies 12,13 . The presence of a correlation between macroprolactin and total prolactin in women with macroprolactinemia indicates that both variables were reciprocally related.…”
Section: Discussionmentioning
confidence: 78%
“…Subjects with diabetes and elevated levels of big‐big prolactin were characterized by higher values of glycated hemoglobin than their counterparts with diabetes and prolactin levels within the reference range 9 . Irrespective of sex, the presence of macroprolactinemia increased circulating levels of cardiometabolic risk factors, 10,11 as well as impaired lipid‐lowering and pleiotropic effects of statins and fibrates 12,13 …”
mentioning
confidence: 99%
“…These pleiotropic effects partially explain why fibrate treatment may bring cardiovascular benefits, which are observed mainly in subjects with atherogenic dyslipidaemia 4,5 . Unfortunately, some endocrine disorders may negatively affect extra‐lipid properties of hypolipidaemic agents 6‐11 . Previous studies showed that pleiotropic effects of fenofibrate were attenuated by thyroid hypofunction, 9 elevated levels of monomeric prolactin 10 and macroprolactinemia, 11 despite the fact that these studies included only patients with mild or moderate forms of these disorders (for ethical reasons subjects with overt hypothyroidism and severe prolactin excess were excluded).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, some endocrine disorders may negatively affect extra‐lipid properties of hypolipidaemic agents 6‐11 . Previous studies showed that pleiotropic effects of fenofibrate were attenuated by thyroid hypofunction, 9 elevated levels of monomeric prolactin 10 and macroprolactinemia, 11 despite the fact that these studies included only patients with mild or moderate forms of these disorders (for ethical reasons subjects with overt hypothyroidism and severe prolactin excess were excluded). However, if hypothalamic–pituitary–thyroid axis activity or prolactin concentrations were normalized by levothyroxine or dopamine agonist treatment, 9,10 the strength of pleiotropic effects of fenofibrate did not differ in comparison to subjects with intact hypothalamic–pituitary–thyroid axis activity or intact lactotroph function.…”
Section: Introductionmentioning
confidence: 99%